The untapped potential of global climate funds for investing in social protection - Mariya Aleksandrova (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
Social protection plays a central role in achieving several of the social and environmental goals of the 2030 Agenda for Sustainable Development. As a result, this policy area is gaining increased recognition at the nexus of global climate change and development debates. Various social protection instruments are deemed to have the potential to increase the coping, adaptive and transformative capacities of vulnerable groups to face the impacts of climate change, facilitate a just transition to a green economy and help achieve environmental protection objectives, build intergenerational resilience and address non-economic climate impacts. Nevertheless, many developing countries that are vulnerable to climate change have underdeveloped social protection systems that are yet to be climate proofed. This can be done by incorporating climate change risks and opportunities into social protection policies, strategies and mechanisms. There is a large financing gap when it comes to increasing social protection coverage, establishing national social protection floors and mainstreaming climate risk into the sector. This necessitates substantial and additional sources of financing. This briefing paper discusses the current and future potential of the core multilateral climate funds established under the United Nations Framework Convention on Climate Change (UNFCCC) in financing social protection in response to climate change. It further emphasises the importance of integrating social protection in countries' Nationally Determined Contributions (NDCs) to access climate finance and provides recommendations for governments, development cooperation entities and funding institutions. To date, investments through the Green Climate Fund (GCF), the Adaptation Fund (AF), and the Global Environment Facility (GEF) for integrating climate change considerations into social protection programmes, policies and mechanisms are generally lacking, even though social transfers and subsidies have often been used to implement climate change projects. Yet, these climate funds can support governments in mainstreaming climate risk into social protection-related development spheres and aligning social security sectoral objectives with national climate and environmental strategies. This, in turn, can help countries increase their capacity to tackle the social and intangible costs of climate change. This paper makes the following recommendations: Funding institutions should make explicit reference to opportunities for financing projects on social protection under their mitigation and risk management portfolios. National governments and international cooperation entities should use climate funds to invest in strengthening social protection systems, work towards improved coordination of social protection initiatives, and utilise the potential of NDCs for climate-proofing the social protection sector. Proponents of social protection should make the most of two major opportunities to boost climate action in the social protection domain: the 2021 United Nations Climate Change Conference (COP26) and the momentum to build back better after the COVID-19 crisis.
Keywords: 330